Total value of phosphorus recovery - Mayer, B.K.; Baker, L.A.; Boyer, T.H.; Drechsel, Pay; Gifford, M.; Hanjra, Munir A. (American Chemical Society, 2016)
Phosphorus (P) is a critical, geographically concentrated, nonrenewable resource necessary to support global food production. In excess (e.g., due to runoff or wastewater discharges), P is also a primary cause of eutrophication. To reconcile the simultaneous shortage and overabundance of P, lost P flows must be recovered and reused, alongside improvements in P-use efficiency. While this motivation is increasingly being recognized, little P recovery is practiced today, as recovered P generally cannot compete with the relatively low cost of mined P. Therefore, P is often captured to prevent its release into the environment without beneficial recovery and reuse. However, additional incentives for P recovery emerge when accounting for the total value of P recovery. This article provides a comprehensive overview of the range of benefits of recovering P from waste streams, i.e., the total value of recovering P. This approach accounts for P products, as well as other assets that are associated with P and can be recovered in parallel, such as energy, nitrogen, metals and minerals, and water. Additionally, P recovery provides valuable services to society and the environment by protecting and improving environmental quality, enhancing efficiency of waste treatment facilities, and improving food security and social equity. The needs to make P recovery a reality are also discussed, including business models, bottlenecks, and policy and education strategies.